Breastfeeding outcomes in European NICUs: impact of parental visiting policies. Issue 2 (19th March 2019) - Cuttini, Marina; Croci, Ileana; Toome, Liis; Rodrigues, Carina; Wilson, Emilija; Bonet, Mercedes; Gadzinowski, Janusz; Di Lallo, Domenico; Herich, Lena Carolin; Zeitlin, Jennifer
Abstract : Objective: The documented benefits of maternal milk for very preterm infants have raised interest in hospital policies that promote breastfeeding. We investigated the hypothesis that more liberal parental policies are associated with increased breastfeeding at discharge from the neonatal unit. Design: Prospective area-based cohort study. Setting: Neonatal intensive care units (NICUs) in 19 regions of 11 European countries. Patients: All very preterm infants discharged alive in participating regions in 2011–2012 after spending >70% of their hospital stay in the same NICU (n=4407). Main outcome measures: We assessed four feeding outcomes at hospital discharge: any and exclusive maternal milk feeding, independent of feeding method; any and exclusive direct breastfeeding, defined as sucking at the breast. We computed a neonatal unit Parental Presence Score (PPS) based on policies regarding parental visiting in the intensive care area (range 1–10, with higher values indicating more liberal policies), and we used multivariable multilevel modified Poisson regression analysis to assess the relation between unit PPS and outcomes. Results: Policies regarding visiting hours, duration of visits and possibility for parents to stay during medical rounds and spend the night in unit differed within and across countries. After adjustment for potential confounders, infants cared for in units with liberal parental policies (PPS≥7) were about twofold significantly more likely to be discharged with exclusive maternal milk feeding and exclusive direct breastfeeding. Conclusion: Unit policies promoting parental presence and involvement in care may increase the likelihood of successful breastfeeding at discharge for very preterm infants.